2017
DOI: 10.1097/coc.0000000000000135
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Correlate of Cardiac-Specific Survival Among Patients Undergoing Coronary Artery Stenting After Thoracic Radiotherapy for Cancer

Abstract: Prior heart and lung-directed RT had volume-dependent and dose-dependent adverse effects on long-term cardiac outcomes for patients subsequently treated with PCI. RT planning that minimizes heart and lung irradiation doses should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Radiotherapy for breast cancer involves exposing the heart to 1–5 Gy [15], [25], [26], [27] levels that cause mainly ischemic heart disease, which tends to occur 10 years or more after the radiation [15], [28], [29]. The dose to and the volume of heart irradiated influence the incidence, type, severity, and mortality associated with RICC [15], [30], [31]. Patients with EC are typically older, are more likely to have pre-existing cardiac disease, and receive much higher heart doses than patients with breast cancer or Hodgkin lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiotherapy for breast cancer involves exposing the heart to 1–5 Gy [15], [25], [26], [27] levels that cause mainly ischemic heart disease, which tends to occur 10 years or more after the radiation [15], [28], [29]. The dose to and the volume of heart irradiated influence the incidence, type, severity, and mortality associated with RICC [15], [30], [31]. Patients with EC are typically older, are more likely to have pre-existing cardiac disease, and receive much higher heart doses than patients with breast cancer or Hodgkin lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with EC are typically older, are more likely to have pre-existing cardiac disease, and receive much higher heart doses than patients with breast cancer or Hodgkin lymphoma. Thus, RICC may begin quite early and manifest in different ways, including pericardial effusion, ischemic heart disease, pericarditis, arrhythmia, or congestive heart failure [9], [10], [19], [31]. Ishikura et al, analyzing long-term toxicity among 78 patients with cancer of the thoracic esophagus, found that 16 (21%) had pericarditis and 2 (3%) had congestive heart failure [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, a separate analysis of 76 patients with radiation-associated CAD suggested, there may be a dose-dependent effect of thoracic XRT on subsequent cardiac-event-free survival. 26 A recent, large study of 1713 survivors of Hodgkin lymphoma, among whom 429 were treated with XRT, found that patients treated with both chemotherapy and XRT had the greatest incidence of cardiovascular disease. 5 Although our results are consistent with the findings in this study, long-term and cardiovascular mortality were not specifically reported, and outcomes after PCI were not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The lungs and the heart are the two main organs at risk in thoracic radiotherapy. Previous studies have shown the detrimental effects of higher lung or heart radiation dose-volumes in lung cancer radiotherapy [1218]. However, the radiotherapy protocol in esophageal cancer is different from that in lung cancer in terms of central location of target volume, wherein it may contribute to high radiation dose-volume of lung or heart (Additional file 1: Figure S1).…”
Section: Introductionmentioning
confidence: 99%